Segregation in social networks based on acquaintanceship and trust - Thomas A. DiPrete; Andrew Gelman; Julien Teitler; Tian Zheng; Tyler McCormick (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2008)
Using newly collected data from the General Social Survey, we compare levels of segregation by race and along other potential dimensions of social cleavage for ties defined in terms of trust and acquaintanceship. We further estimate the size of the trust network and compare its size and structure to recent estimates obtained from the 2004 General Social Survey by McPherson et al. Americans are less disconnected than other recent evidence suggests. However, if racial segregation is the standard, then America is highly segregated across class and values dimensions as well as race and ethnicity. We further find that segregation is insensitive to tie strength. Scholars have long found homophily in close ties, while scholars such as Putnam have looked to weak ties for socially integrative 'bridging' social capital. However, 'bridging' social capital does not appear to be more plentiful for weak ties than it is for strong ties.
Keywords: 300; Segregation; Soziales Netzwerk; Soziale Integration; Vertrauen; USA